2016
DOI: 10.1111/ijau.12075
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fair Value Measurement on Audit Fees: Evidence from Financial Institutions in 24 European Countries

Abstract: The purpose of the study is to investigate the relationship between fair value measurement and audit fees. Using a sample of 177 banks from 24 European countries over the period 2008–13, we find that high uncertainty fair value assets are positively related to audit fees. The result is consistent with the suggestion that more complex estimates require greater audit effort. To provide more insight into the impact of fair value measurement on audit fees, we examine this relation under institutional settings with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 50 publications
(158 reference statements)
9
39
3
1
Order By: Relevance
“…However, not all studies considered in our literature analysis aim to investigate the direct effect of institutional attributes on auditing. Instead, some examine the moderating role of such country factors on documented associations in audit practice (e.g., Alexeyeva & Meijka‐Likosova, 2016; Kuo & Lee, 2018). These studies deepen our understanding of how country factors affect auditor behaviour and, in turn, audit pricing.…”
Section: Potential Country‐level Determinants Of Audit Fees: Review Of Prior Cross‐country Literaturementioning
confidence: 99%
“…However, not all studies considered in our literature analysis aim to investigate the direct effect of institutional attributes on auditing. Instead, some examine the moderating role of such country factors on documented associations in audit practice (e.g., Alexeyeva & Meijka‐Likosova, 2016; Kuo & Lee, 2018). These studies deepen our understanding of how country factors affect auditor behaviour and, in turn, audit pricing.…”
Section: Potential Country‐level Determinants Of Audit Fees: Review Of Prior Cross‐country Literaturementioning
confidence: 99%
“…For example, Ettredge, Xu, and Yi () showed that there is a fee premium for auditing the fair values that increases with the estimation uncertainty. Alexeyeva and Mejia‐Likosova () and Yao, Percy, and Hu () presented similar evidence for European and Australian datasets respectively . By using the abnormal audit fees, we investigate the bank‐specific fee premium that the auditor charges on top of the average fee premium (the firm‐specific discount on the average fee premium) and control for several other distorting effects…”
Section: Background and Hypotheses Developmentmentioning
confidence: 64%
“…This model uses the audit fees as a function of the bank's attributes of size; credit, market, liquidity, business, and capital risks; and auditor‐specific variables. We follow Ettredge et al () and Alexeyeva and Mejia‐Likosova () and extend this model by adding the proportion of the fair‐value assets at each level of the fair‐value hierarchy . In including fair‐value variables in the audit fee model, we assume that the fee premium can be separated into two components.…”
Section: Empirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We source audit fees and firm-specific financial data from the Thom- We begin with an initial sample of 251,834 firm-year observations with non-missing audit fees data from 44 countries spanning 2001 to 2017. We drop 24,234 (4,874) firm-years from the financial (utility) industries based on the four-digit Global Industry Classification Standards (GICS), because the audit fee determinants for such industries are distinct (e.g., Alexeyeva & Mejia-Likosova, 2016). We derive a sample of 164,964 firm-year observations after merging with the organization capital database.…”
Section: Data and Samplementioning
confidence: 99%